2010
DOI: 10.1111/j.1439-0310.2009.01729.x
|View full text |Cite
|
Sign up to set email alerts
|

Eavesdropping and Risk Assessment Between Lions, Spotted Hyenas and African Wild Dogs

Abstract: Vocalizing allows rapid transmission of detailed information beyond line of sight. However, the risk of eavesdropping by unintended receivers means there is also a potential cost to any vocalization. For fugitive species such as African wild dogs the potential cost of attracting dangerous competitors as eavesdroppers is especially significant. Experiments presented here demonstrate that eavesdropping lions Panthera leo were highly motivated to approach playbacks of wild dog Lycaon pictus vocalizations. As lion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 27 publications
2
16
0
1
Order By: Relevance
“…At least one hyaena came to the broadcast site in 25 of the 40 trials (63%), and the mean number of respondents for successful call-ins was five. As in previous studies (Ogutu & Dublin, 1998; Ogutu et al, 2005; Webster, McNutt, & McComb, 2010), hyaenas responded strongly to the call-ins and consistently arrived at broadcast sites behaving as though they regarded the stimuli as evidence of a highly salient event. Call-ins drew hyaenas from more than a kilometre away (as observed in multiple trials where distant resting hyaenas were observable from the broadcast site).…”
Section: Resultssupporting
confidence: 79%
“…At least one hyaena came to the broadcast site in 25 of the 40 trials (63%), and the mean number of respondents for successful call-ins was five. As in previous studies (Ogutu & Dublin, 1998; Ogutu et al, 2005; Webster, McNutt, & McComb, 2010), hyaenas responded strongly to the call-ins and consistently arrived at broadcast sites behaving as though they regarded the stimuli as evidence of a highly salient event. Call-ins drew hyaenas from more than a kilometre away (as observed in multiple trials where distant resting hyaenas were observable from the broadcast site).…”
Section: Resultssupporting
confidence: 79%
“…Eavesdropping is a widespread phenomenon and occurs in many different species like mammals (e.g. [23][25]), birds (e.g. [26][30]), amphibians [31], fish (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Attracting unwanted attention can potentially be deadly. Larger predators often kill smaller competitor species and playbacks of African wild dog vocalisation have shown that lion actively move towards their location [40], while African wild dogs move away from lion calls [41]. Considering the vulnerability of cheetah to a range of predators it is unlikely that long periods of vocalisation are used for long distance communication and the chirping sound carries far less than lion roars [21] or wolf howls [42].…”
Section: Resultsmentioning
confidence: 99%